The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1038/nature09093
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency with single atoms in a cavity

Abstract: Optical nonlinearities offer unique possibilities for the control of light with light. A prominent example is electromagnetically induced transparency (EIT), where the transmission of a probe beam through an optically dense medium is manipulated by means of a control beam. Scaling such experiments into the quantum domain with one (or just a few) particles of light and matter will allow for the implementation of quantum computing protocols with atoms and photons, or the realization of strongly interacting photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
273
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(290 citation statements)
references
References 36 publications
7
273
2
2
Order By: Relevance
“…This work was triggered by recent experimental studies of single photon EIT [25,26], where long trap lifetimes times have been observed [26], indicating robust cooling in this system, and on recent theoretical studies [27] of cooling in this experimental setup. Here, we demonstrate cavity-assisted EIT cooling of an atom in a dipole trap.…”
Section: Introductionmentioning
confidence: 99%
“…This work was triggered by recent experimental studies of single photon EIT [25,26], where long trap lifetimes times have been observed [26], indicating robust cooling in this system, and on recent theoretical studies [27] of cooling in this experimental setup. Here, we demonstrate cavity-assisted EIT cooling of an atom in a dipole trap.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent processes leading to EIT and ATS have been studied in: atomic gases 7,13 , atomic and molecular systems 14 , solid-state systems 15 , superconductors 16,17 , plasmonics 18 , metamaterials 19 , optomechanics 20,21 , electronics 22 , photonic crystals 23 and whispering-gallery-mode microresonators (WGMRs) [24][25][26][27][28][29][30][31][32][33] . Systems in which EIT and ATS have been studied are listed in Fig.…”
mentioning
confidence: 99%
“…It is well-known that quantum coherence can drastically change the optical properties of a medium; in particular, absorption can practically vanish even at the single atom-photon level [13].…”
mentioning
confidence: 99%